Nonlinear Behavior Study of Reinforced Concrete Coupling Beams Subjected to the Effect of Wind Loading - Sarah Bashour; Bassam Hwaija; Fadwa Issa (Advances in Civil Engineering)
Reinforced concrete shear walls connected by coupling beams are considered an efficient structural system for tall buildings subjected to lateral loads. For seismic design of such buildings, performance-based design has been commonly used in regions with strong earthquakes for its ability to achieve economical and safe design, however the use of performance-based wind design (PBWD), which permits nonlinear response of ductile elements at specific locations under wind loads is still hindered due to the lack of information regarding the performance of these elements. In addition to that, there is still a need for developing an analytical model that can represent nonlinear behavior of these elements when subjected to wind loads. Therefore, in this study two analytical models using two different methods to consider bond slip effect (Bond SP01 (BS) model and steel modification factor (SMF) model) were developed and implemented in OpenSees software and validated with a tested specimen of reinforced concrete coupling beam subjected to a simulated windstorm loading protocol. Then, a parametric study was conducted using the SMF model to investigate the effect of axial restraint, and modification of the ductility demand. Results showed that both of the models showed good agreement with the experiment, however results of the SMF model were more accurate. As for the parametric study, it was concluded that with axial restraint, the beam behavior was dominated by shear, and a slight increase of strength was observed. At ductility demand of 1.8θy, the beam performed well with no significant damage and minor residual rotations.